2013
DOI: 10.1007/s11010-013-1642-6
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol up-regulates miR-155 expression and reduces TP53INP1 expression in MCF-7 breast cancer cells

Abstract: In estrogen responsive breast cancer cells, estradiol (E2) is a key regulator of cell proliferation and survival. MiR-155 has emerged as an "oncomiR", which is the most significantly up-regulated miRNA in breast cancer. Moreover, miR-155 is higher in ERα (+) breast tumors than ERα (-), but no one has examined whether E2 regulates miR-155 expression in MCF-7 cells. In this study, the aim was to explore whether miR-155 involved in E2 regulated expression of estrogen responsive genes. We evaluated miR-155 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…In particular, miR-155 has been shown to be overexpressed in breast cancers (26)(27)(28) and is modulated by estrogens (29). In addition, miR-155 controls miR-143 expression, a miRNA known to target HK2 in MCF7 cells (30).…”
Section: Er-dependent Mir-155 Is Responsible For Metabolic and Motilementioning
confidence: 99%
“…In particular, miR-155 has been shown to be overexpressed in breast cancers (26)(27)(28) and is modulated by estrogens (29). In addition, miR-155 controls miR-143 expression, a miRNA known to target HK2 in MCF7 cells (30).…”
Section: Er-dependent Mir-155 Is Responsible For Metabolic and Motilementioning
confidence: 99%
“…We have accomplished the appropriate concentration of E 2 assay in our previous study (Zhang et al, 2013). The effect of E 2 on promoting proliferation of MCF-7 cells was investigated with CCK-8 assay and the concentration (100 nmol/L) of E 2 in the following experiments was determined according to the rate of proliferation.…”
Section: Concentration Of 17β-estradiol (E 2 ) Assaymentioning
confidence: 99%
“…Except in rare cases, such as MCF-7 cells, in which a 47-base pair deletion in CASP3 has been identified (8), the reason for loss of caspase-3 is generally unknown. Recently, several studies have proposed a direct posttranscriptional regulation of caspase-3 expression by microRNAs (miRNAs) (9)(10)(11). In particular, overexpression of miR-155 has been associated with downregulation of caspase-3 and resistance to apoptosis in the caspase-3-deficient breast cancer cell line MDA-MB-157 (10,11).…”
mentioning
confidence: 99%
“…Recently, several studies have proposed a direct posttranscriptional regulation of caspase-3 expression by microRNAs (miRNAs) (9)(10)(11). In particular, overexpression of miR-155 has been associated with downregulation of caspase-3 and resistance to apoptosis in the caspase-3-deficient breast cancer cell line MDA-MB-157 (10,11). In their study, Lin et al demonstrated that upregulation of another miRNA, let-7a-1, decreases caspase-3 expression and is associated with significant accumulation of the XIAP:p19/ p12-CASP7 complex and enhanced chemoresistance (4).…”
mentioning
confidence: 99%